Объяснение:
[tex]\sqrt[3]{x}=x^{\frac{1}{3}}=x^{\frac{2}{6}}=(x^{\frac{1}{6}})^2=(\sqrt[6]{x})^2[/tex]
Упрощаем выражение:
[tex]\frac{\sqrt[3]{a}\sqrt[6]{b}+\sqrt[3]{b}\sqrt[6]{a}}{\sqrt[6]{a}\sqrt[6]{b}+\sqrt[3]{b}}=\frac{(\sqrt[6]{a})^2*\sqrt[6]{b}+(\sqrt[6]{b})^2\sqrt[6]{a}}{\sqrt[6]{a}\sqrt[6]{b}+(\sqrt[6]{b})^2}=\frac{\sqrt[6]{a}\sqrt[6]{b}(\sqrt[6]{a}+\sqrt[6]{b})}{\sqrt[6]{b}(\sqrt[6]{a}+\sqrt[6]{b})}=\sqrt[6]{a}[/tex]
Ответ:
[tex]\sqrt[6]{a}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Объяснение:
[tex]\sqrt[3]{x}=x^{\frac{1}{3}}=x^{\frac{2}{6}}=(x^{\frac{1}{6}})^2=(\sqrt[6]{x})^2[/tex]
Упрощаем выражение:
[tex]\frac{\sqrt[3]{a}\sqrt[6]{b}+\sqrt[3]{b}\sqrt[6]{a}}{\sqrt[6]{a}\sqrt[6]{b}+\sqrt[3]{b}}=\frac{(\sqrt[6]{a})^2*\sqrt[6]{b}+(\sqrt[6]{b})^2\sqrt[6]{a}}{\sqrt[6]{a}\sqrt[6]{b}+(\sqrt[6]{b})^2}=\frac{\sqrt[6]{a}\sqrt[6]{b}(\sqrt[6]{a}+\sqrt[6]{b})}{\sqrt[6]{b}(\sqrt[6]{a}+\sqrt[6]{b})}=\sqrt[6]{a}[/tex]
Ответ:
[tex]\sqrt[6]{a}[/tex]